Pengaruh Pelaksanaan Self Assesment System dan Pengetahuan Perpajakan Terhadap Kepatuhan Wajib Pajak Orang Pribadi (Studi pada Kantor Pelayanan Pajak Pratama Jakarta - Cakung) - Wijaya, Elisabet Natalia; Kurniawan, Budi (UNIVERSITAS KALBIS, 2025)
Indonesia as a developing country is intensively developing infrastructure in variousregions to support economic and socio-cultural development. In essence, all developments carried out will be financed by the State Budget (APBN) and the Regional Budget (APBD) which comes from state tax revenue. Tax is a very basicthing, in the procedure for collecting taxes mustbe based on laws and regulations. In essence, those who bear the tax burden are the people. The issue of tax base and tax rate must gothrough the consent of the people represented bythe people's representative institution and theresult of the approval is described in a law thatmust be obeyed by all parties subject to taxobligations. In the Self Assessment systemeverything related to the amount of tax payable must be left entirely to the taxpayer and the success of this Self Assessment System dependslargely on the compliance of the taxpayer.